Two-photon calcium imaging from motion-sensitive neurons in head-fixed Drosophila during optomotor walking behavior - Seelig, Johannes D. (2010)
Drosophila melanogster is a model organism rich in genetic tools to manipulate and identify neural circuits involved in specific behaviors. Here we present a novel technique for two-photon calcium imaging in the central brain of head-fixed Drosophila walking on an air-supported ball. The ball’s motion is tracked at high resolution and can be treated as a proxy for the fly’s own movements. We used the genetically encoded calcium sensor, GCaMP3.0, to record from important elements of the motion-processing pathway, the horizontal-system (HS) lobula plate tangential cells (LPTCs) in the fly optic lobe. We presented motion stimuli to the tethered fly and found that calcium transients in HS-neurons correlated with robust optomotor behavior during walking. Our technique allows an entirely new set of questions to be addressed by monitoring behavior and physiology in identified neurons in a powerful genetic model organism with an extensive repertoire of walking behaviors.